Efficient power allocation for MIMO CR-NOMA networks - Abidrabbu, Shaima; Arslan, Hüseyin (Institute of Electrical and Electronics Engineers Inc., 2021)
Cognitive radio-based non-orthogonal multiple access (CR-NOMA) is considered to be one of the promising multiple accessing technique candidates for 5G and beyond networks. These networks are facing a lot of challenges to achieve high spectral efficiency, low latency, and massive connectivity. Interference management and efficient power allocation are highly interesting among the researchers to investigate in CR-NOMA networks. This paper studies the power allocation of underlay CR-NOMA networks using multi-input multi-outputs (MIMO) techniques to increase the achievements of getting higher spectral efficiency as well as spatial diversity among multiple users to be served. In particular, power allocation based on uniform and adaptive power allocation, and near-optimal for high and low signal to noise ratio are derived. Finally, the simulation results show the superiority of the proposed scheme in achieving higher spectral efficiency, fairness, and average capacity of secondary users compared to the conventional scheme.
Keywords: CR-NOMA; Fairness; MIMO; Power Allocation; Spectrum Efficiency